Facile Synthesis and Electrochemical Studies of Mn2O3/Graphene Composite as an Electrode Material for Supercapacitor Application - Mustafa, Ghulam; Mehboob, Gohar; Khisro, Said Nasir; Javed, Muhammad; Chen, Xinman; Ahmed, M. Shafiq; Ashfaq, J. M.; Asghar, G.; Hussain, Shahnwaz; Rashid, Amin ur; Mehboob, Ghazanfar (Frontiers in Chemistry, 2021)
Simplified sol-gel method that can be scaled up for large scale production was adopted for the preparation of manganese oxide nanocrystals. Prepared material exhibited micron sized particles with nano porous structure. Nano porous materials provide better electrolyte-electrode interface with larger specific area and are ideal candidates for energy storage applications. The morphology and crystalline structure of the prepared material was investigated by scanning electron microscopy (SEM), X-Ray diffraction (XRD), and Energy-dispersive X-ray spectroscopy, (EDX). Furthermore, different ratios of Mn2O3/graphene nanocomposites were deposited on nickel foam substrate to study composition dependent electrochemical properties. The cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and complex impedance studies confirm excellent capacitive behaviour and specific capacitance for the prepared material.